2010
DOI: 10.1111/j.1464-5491.2009.02915.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of targeting normal fasting glucose levels with basal insulin glargine on glycaemic variability and risk of hypoglycaemia: a randomized, controlled study in patients with early Type 2 diabetes

Abstract: Treatment to target of FPG < 5.3 mmol/l with insulin glargine was not associated with significantly increased risk of hypoglycaemia. Strict control of FPG with insulin glargine was effective to control postprandial glucose excursion, but had no significant effect on sd and MAGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 18 publications
(15 reference statements)
5
28
2
1
Order By: Relevance
“…A common hypothesis attributed the excess mortality to the higher rate of hypoglycemia in the intensified treatment group. However, as demonstrated by our group using continuous glucose monitoring, the rate of hypoglycemia is not inevitably related to A1C (23). Interestingly, some new post hoc analyses of the ACCORD study, which has been terminated early because of excess mortality in the intensified treatment arm, indicated a decrease of cardiovascular mortality in patients who indeed reached the target A1C value of 6.0% under intensified treatment (24).…”
Section: Effects Of Blood Glucose Lowering On Cardiovascular Events Imentioning
confidence: 88%
“…A common hypothesis attributed the excess mortality to the higher rate of hypoglycemia in the intensified treatment group. However, as demonstrated by our group using continuous glucose monitoring, the rate of hypoglycemia is not inevitably related to A1C (23). Interestingly, some new post hoc analyses of the ACCORD study, which has been terminated early because of excess mortality in the intensified treatment arm, indicated a decrease of cardiovascular mortality in patients who indeed reached the target A1C value of 6.0% under intensified treatment (24).…”
Section: Effects Of Blood Glucose Lowering On Cardiovascular Events Imentioning
confidence: 88%
“…The early start of basal insulinization especially with longer-acting basal insulin seems more and more appropriate according to experimental data, for example, regeneration of the first phase and improvement of the second phase of insulin secretion [Pennartz et al 2011], pooled analysis of prospective randomized clinical trials [Fonseca et al 2011], observational trials, for example, EARLY [Hanefeld et al 2012[Hanefeld et al , 2014, a recently published open-label, randomized, prospective trial comparing the effects of insulin glargine versus metformin [Pistrosch et al 2013], and the large and long-term randomized controlled trial (RCT) ORIGIN [Hanefeld et al 2010;Gerstein et al 2012]. The concept of early insulinization with basal insulin (after metformin therapy is initiated or if metformin is contraindicated) is also supported by Saxonian [Fachkommission Diabetes Sachsen, 2009;Rothe et al, 2010] and German national guidelines [Nationale Versorgungsleitlinie Diabetes, 2014], international position statements [Inzucchi et al 2012] and clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, control of basal glycemia is the most efficacious way to treat postprandial glycemia [5]. Nevertheless, in patients treated with basal insulin and in cases where the glycemic profile shows a clear predominance of prandial hyperglycemia, a drug with a more specific action against this abnormality could prove useful.…”
Section: Discussionmentioning
confidence: 99%
“…In patients treated with oral antihyperglycemic drugs, Riddle et al [4] showed that the relative contribution of basal hyperglycemia to HbA1c was 76–80% before intensification with insulin and 31.5–41% after 24–28 weeks of treatment with basal insulin. Moreover, since the main determinant of postprandial hyperglycemia is preprandial hyperglycemia, treatment of basal hyperglycemia is the most efficacious way to control postprandial hyperglycemia [5]. Finally, most major studies on the efficacy of glycemic control are based on fasting blood glucose and HbA1c targets.…”
Section: Introductionmentioning
confidence: 99%